PENGARUH KUALTAS PRODUK, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA KLINIK KECANTIKAN ELLA SKIN CARE - Hartatik, Hartatik; Susanti, Ari (Jurnal Akuntansi dan Bisnis, 2022)
Ella skin care clinic was first established by dr. Elia Gunawan in Solo, Central Java on May 9, 2008. Ella skincare is a clinic that focuses on skin care and beauty by combining high quality ingredients from nature and medical. All selected ingredients from nature can be absorbed by the skin perfectly and are able to provide maximum results with the help of technology. Several types of treatments at Ella skin care use real flowers and not just extracts, that is to really get the best results. The purpose of this study is to examine and describe the impact of product quality, service quality and price on consumer satisfaction at the Ella skincare beauty clinic. The sample used was purposive sampling technique with a total of 96 respondents. The processed questionnaire was used as a data collection technique for further processing using SPSS. Multiple linear regression was used as a data analysis tool. The results of this study indicate that the quality of a product does not partially affect a purchasing decision. While the quality of service and price have a positive and significant effect on consumer satisfaction at the Ella skin care beauty clinic. Simultaneously, the variables of product quality, service quality and price have a significant effect on consumer satisfaction at Ella skin care beauty clinic. Consumer satisfaction can be explained by the variable price, product quality and service quality by 74.7% and the rest is explained by other variables not listed in this study.Keywords: Product Quality, Price, Service Quality.